THE ROLE OF PRAGMATIC COMPETENCE IN INTERCULTURAL COMMUNICATION - Shamsutdinova L.R. (Western European Studies, 2025)
The article examines the role of pragmatic competence in teaching foreign languages, emphasizes the importance of taking into account pragmalinguistic and sociopragmatic norms in the development of intercultural communication. Special attention is paid to the problem of interlanguage transfer and its impact on the success of communication. Examples of pragmatic difficulties caused by differences in the use of speech acts such as "advice" are presented. The study concludes that students must develop skills to use pragmatic competence in accordance with the norms of the language being studied in order to prevent communicative failures.
Keywords: Pragmatic competence; intercultural communication; cross-linguistic transfer